The Influence of Teacher-Student Relationships on Mathematics Problem-solving - Louida Penera Patac; Adriano Villarosa Patac Jr.; Shiela Gales (International Journal on Emerging Mathematics Education, 2021)
Literatures revealed that the cognitive and affective components are the factors affecting problem solving. In this article we identified factors considered by the students in learning mathematical problem solving. Using a descriptive phenomenological research we identified the lived experiences of forty-five (45) students in solving a mathematics problem. Following the Colaizzi method for data analysis, four themes emerged: emotions and self- efficacy as affective factors, and group learning activity and teacher- student relationship as social factors. Sixty items from these four themes were further explored in using an Exploratory Factor Analysis (EFA) for a new set of 200 students. These four-factor structures of the students experiences in mathematics problem solving explained 66% of the variance in the pattern of relationships among the items. All four-factor structures had high reliabilities (all at or above Cronbachs Î± > .904). The study exemplified that teacher- student interaction relationship during learning activities, which is a social factor, provides the highest correlated factor that influences the mathematical performance of the students.